Terrestrial Gastropods at the UWM Cedar-Sauk Field Station - (:unkn) unknown (My University, 1980)
A base line survey of the terrestrial gastropod fauna of the UWM Field Station near Saukville was conducted from June-September 1978 to complement other faunistic surveys conducted at this locality and to increase our information on the distribution of these mollusks in southeastern Wisconsin. To date there have been very few surveys of terrestrial gastropods in southeastern Wisconsin. In this survey 2975 specimens of 20 different identities were retrieved.
Keywords: terrestrial Gastropods; mollusks; snails; slugs